Problem for Panmen in Finding Homes - Unknown (Trinidad Guardian)
In Trinidad and Tobago, several steelbands are desperately looking for new headquarters and have sought the assistance of their umbrella organization, Pan Trinbago, which is working feverishly on a draft plan for a pan theatre to present to the Ministry of Education and Culture.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago